2017
DOI: 10.1051/matecconf/201710905003
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Coal Slagging Characteristics and Combustion Behaviour in Furnace

Abstract: Abstract. This paper describes an investigation of coal characteristics and slagging potential using coal slagging assessment tool such as numerical slagging indices. Historical data on coal use according to type and shipment in power plant was use for the analysis. It is found that higher content of silica oxide results in higher softening temperature and the monomers modifiers can alter the softening temperature. Calculation also reveals encouraging conditions that could possibly prevent the slagging potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Low fusibility could increase slagging potential [13]. SRF also has low SiO2 and high CaO content, which can cause slagging and fouling [13][14][15]. In addition, it was also found that the chlorine content in SRF was very high at 5442 ppm.…”
Section: Characteristic Of Fuelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low fusibility could increase slagging potential [13]. SRF also has low SiO2 and high CaO content, which can cause slagging and fouling [13][14][15]. In addition, it was also found that the chlorine content in SRF was very high at 5442 ppm.…”
Section: Characteristic Of Fuelsmentioning
confidence: 99%
“…Low AFT could decrease fusibility. Low fusibility could increase slagging potential [13]. SRF also has low SiO2 and high CaO content, which can cause slagging and fouling [13][14][15].…”
Section: Characteristic Of Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Source: Frandsen, 1997) Each coal type was then tested to identify the respective characteristic using the ultimate analysis and approximate analysis method. The respective coal was then further analyzed to quantify its calorific value, carbon, hydrogen, nitrogen, oxygen, ash content inside the coal [5,19]. The Hard Grove Index (HGI) for each specific coal was subsequently tested to determine the coal hardness before firing at the plant [4].…”
Section: Figure 3 Schematic Diagram Process For Thermal Coal Fired Power Plantmentioning
confidence: 99%
“…Hal tersebut konsisten pada delapan sampel batu bara subbituminous yang tergolong LRC. [5] [6] [7] Babcock & Wilcox (selanjutnya disingkat B&W) sebagai perusahaan manufaktur boiler yang berasal dari negara USA telah mengembangkan beberapa slagging indice untuk berbagai aspek pada desain boiler. Slagging indice akan menentukan kriteria desain furnace dan area radiasi lainnya.…”
unclassified